Wrs. jubileum accountantskantoor De Wolff en Van Meurs. De Wolff in het midden vooraan, naast hem zijn vrouw
Wrs. jubileum accountantskantoor De Wolff en Van Meurs. De Wolff in het midden vooraan, naast hem zijn vrouw.